Moisture sorption of biochar from banana pseudostem fibers according to the pyrolysis temperature - Dias, Diogenes dos Santos [UNESP]; Faria, Flaviana Andrade [UNESP]; Mattiolli, Lucas [UNESP]; Capela, Marisa Veiga [UNESP]; Capela, Jorge Manuel Vieira [UNESP]; Crespi, Marisa Spirandeli [UNESP]; Ribeiro, Clovis Augusto [UNESP] (Springer Nature, 2019)
Biomass has been widely used mainly for power generation or fertilizer and can be used in natura, torrefied or pyrolyzed form. For application in the generation of energy or fertilizer, it is necessary the knowledge of some properties such as the sorption of moisture. The main aim was to evaluate the sorption of moisture by the fibers from banana pseudostem in natura (wet basis), dry (100 °C), torrefied (200–300 °C) and pyrolyzed (400–600 °C). For the evaluation of the sorption of moisture was used climatized chamber at temperatures of 40 °C and 75% relative humidity (climatic zone IV). The results indicate that under the conditions used, when higher pyrolysis temperature is applied to the biomass, higher sorption of moisture occurs, with values close to 50% (w/w) for banana pseudostem fibers pyrolyzed at 600 °C. The significant increase in moisture was attributed initially by the presence of a high concentration of potassium oxalate that was later converted to carbonate in biochar obtained above 400 °C. In order to characterize the biomasses, thermogravimetry, differential scanning calorimetry, Fourier transform infrared spectroscopy and energy-dispersive spectroscopy were used. The exponential model was used to evaluate the kinetics of moisture sorption.
Keywords: Banana pseudostem fibers; Biochar; Kinetic of sorption; Moisture sorption; Pyrolysis; Torrefaction